THE DESCRIPTIVE STUDY ON THE SECOND YEAR STUDENTS’ INTEREST AND MOTIVATION TOWARD PEER ASSISTED LEARNING PROGRAM (PALP) OF ENGLISH EDUCATION DEPARTMENT AHMAD DAHLAN UNIVERSITY IN ACADEMIC YEAR 2016/2017 - Novi Sri Rahmi; Arilia Triyoga (UAD TEFL International Conference)
The aims of this research are to describe the students’ interest toward PALP, the students’ motivation toward PALP, and to describe the social factors affects to students’ interest and motivation.The type of the research is descriptive research. The research subject was the second semester of PBI students in Ahmad Dahlan University in the academic year 2016/ 2017. There were 10 groups of PALP as the sample. The researcher used questionnaire, observation sheet and interview guide to gather the data. In analyzing the data the researcher used quantitative method.Based on the research, it is found that; first the students’ interest toward PALP is in high category based on impression (75% were agree), confidence (82% were agree in a group of PALP, 85 % were agree in the class), learning atmosphere (84% were agree), excitement (81% were agree), new knowledge (73% were agree) and language skill (78% were agree). Secondly, the students’ motivation toward PALP is in high category based on mentees’ individual competency in PALP based on how often they are expressing opinion (79% were agree), responding the question (80% were agree), and asking question (61% were agree). And the third, there were four social factors affecting students’ interest and motivation. The social factor were positive learning atmosphere (84% were agree), the second was friend (80% were agree). The third was mentor (72% were agree).  The last was the place (55% were agree). The job, gender and distance factor did not affect students’ interest and motivation toward PALP.